Ecosystem Approach to Fisheries Management in Palabuhanratu Nusantara Fishing Port: Evaluation and Development Strategy - Agustian, Dita; Megantara, Erri Noviar; Ihsan, Yudi Nurul; Cahyandito, Martha Fani (Jakarta Technical University of Fisheries, 2023)
Comparison between the usages of fisheries resources and the allowable catch in Indonesia is in the fully exploited category, which means that fishing efforts are maintained with close monitoring. This study aims to analyze whether fisheries management practices, especially in Palabuhanratu Nusantara Fishing Port, have been managed sustainably or not based on indicators in the Ecosystem Approach to Fisheries Management (EAFM), and identify strategies for developing and strengthening fisheries management in the area according to the results of the EAFM evaluation. The method used is a survey method using composite analysis and flag modeling visualization techniques. This method will assess the EAFM indicator as a multi-criteria system that ends in a composite index in the form of a score of values related to the level of achievement or sustainability of fisheries management by EAFM principles. The results show that the mean composite value for all EAFM domains is 66.72 with a good category. Then the strategies for developing and strengthening the sustainability of fisheries management at Palabuhanratu Nusantara Fishing Port are through increasing the status of the port to become an Ocean Fishery Port, increasing the added value of the economy of fishery products, strengthening the regulations with fair law enforcement, optimizing the usage of technology in fisheries management, and strengthening the system fishery business capital. It is hoped that similar research can be carried out at least at the coastal fishing port to ocean fishing port, as one of the bases for determining the sustainability of fisheries management at a wider level.